The impact of ex-auditors' employment with audit clients of perceptions of auditor independence - Ahmad, Maslina (2014)
This study examined whether the practice of ex-auditors’ employment with audit clients affects perceptions of auditor independence from the perspective of financial statement users in Malaysia. It has been argued that the main problem with employment with an audit client is the ability of current auditors to remain independent when dealing with top managers who were previously their fellow auditors. The collapse of Enron in 2001 in the United States, along with other infamous financial scandals like Global Crossing and Waste Management revealed that in each of these companies, the senior accounting and finance officers were hired directly from their external auditors. The results of the study showed that financial statement users are concerned about the practice of ex-auditors seeking employment with audit clients. However, the cooling-off period of 2 years that audit firms must observe before an audit partner joins a client company (otherwise, the firms have to resign from the audit engagement) was perceived as sufficient to safeguard auditor independence. As the majority of respondents seemed to support the current policy, a reduction or an extension of the existing cooling-off period is deemed not necessary.